A GLUTs/GSH cascade targeting-responsive bioprobe for the detection of circulating tumor cells. Issue 24 (4th March 2022) - Wang, Yi; Li, Jiahui; Chen, Zelong; Pu, Liang; Pei, Zhichao; Pei, Yuxin
Abstract : We report a GLUTs/GSH cascade targeting-responsive bioprobe via the coordination of copper ions with a glucose-based coumarin derivative ligand for simple and ultrasensitive detection of circulating tumor cells. Abstract : A GLUTs/GSH cascade targeting-responsive bioprobe, GluCC, was rationally designed and synthesized for the first time via the coordination of copper ions with a glucose-modified coumarin derivative ligand (GluC). GluCC can specifically detect circulating tumor cells (CTCs) in lung metastatic mice models by targeting the Warburg effect and responding to overexpressed glutathione in the tumor microenvironment. This bioprobe with a simple detection procedure has significant advantages for CTC detection.